Contributions of ecological programs to vegetation restoration in arid and semiarid China - Diwen Cai; Quansheng Ge; Xunming Wang; Baoli Liu; Andrew S Goudie; Shi Hu (Environmental Research Letters, 2020)
Over the past four decades, large-scale ecological programs, including the ‘Great Green Wall Program’ (1978–present), ‘Grain for Green Program’ (1999–present), ‘Grassland Ecological Protection Program’ (2000–present), and ‘Beijing-Tianjin Sandstorm Source Control Project’ (2002–present), were launched to restore vegetation, to combat desertification, and to control dust storms in arid and semiarid China. The gross investments of these programs have exceeded 1700 billion RMB (∼260 billion USD, accounting for ∼1% GDP in the region) by now, however, the effects of these programs on vegetation restoration have not been settled. In this study, the vegetation indices, land-uses, and climatic factors were used to estimate the contribution of the above programs on vegetation restoration. The results showed that consistent vegetation restoration has occurred in about 45.3% of the vegetated areas in arid and semiarid China from 1982 to 2000, and the percentage decreased to 33.6% after 2000 despite more ecological programs have been launched. Changes in climatic factors (precipitation, temperature, solar radiation, and wind speed) and elevated atmospheric CO _2 concentration contributed more than 50% and 70% to vegetation restoration in periods of 1982–2000 and 2001–2015, respectively, however, the contribution rate of ecological programs kept stable at about 20%. Climate changes in the past forty years played a dominant role, although the ecological programs showed a noticeable effect on vegetation restoration. Further investment in ecological restoration practices might need to be critically evaluated on the cost-effectiveness.